Technical Efficiency Analysis of Rice Farming (Case Study) - Miftahul Jannah; Nuhfil Hanani; Agustina Shinta Hartati Wahyuningtyas (Jurnal Penelitian Pendidikan IPA, 2024)
Efficiency is an important aspect for farmers as a tool for measuring production decisions regarding available alternatives. There are several differences in efficiency at the operational level, one of which is worth paying attention to is technical efficiency. The aims of this research are, to describe rice farming in Jati Village, Gondang Bojonegoro District, to analyze the technical efficiency of production in rice farming activities in Jari Village, Gondang Bojonegoro District, to analyze the influence of factors on technical efficiency in activities farming in Jari Village, Gondang District, Bojonegoro. The approach used to analyze the data is Data Envelopment Analysis (DEA) and Tobit regression. In the 2023 planting season, farmers are generally worried about climatic factors that are starting to be unpredictable, an uncertain climate will be an obstacle for farmers to plant rice twice, farmers are still not using inputs according to the recommended use, as in use of seeds and fertilizer. Farmers can still reduce seeds by 5.84 kg, fertilizer by 60.01 kg, plant maintenance medicine by 0.40 liters, labor by 3.81 HOK, and use of tractor engines by 94 minutes. Increasing technical efficiency in farming is strongly influenced by socio-economic factors of farmers. The factors that influence the technical efficiency value of rice farming in Jari Village are age and workforce. Efforts to increase rice farming can be done by using production inputs in accordance with the recommended composition of government programs